MULTI-SOURCE MONITORING OF DAIRY FARM MANAGEMENT PRACTICES AND MILK QUALITY ANALYSIS IN AMHARA REGION, ETHIOPIA - BIRHAN, MALEDE; MEKURIAW, YESHAMBEL; TASSEW, ASAMINEW; TEGEGNE, FIREW (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Ethiopians consume less than 20 kilograms of raw milk per year, far less than the African (40 kg) and global averages (105 kg) per year. Dairy price sensitivity has increased as a result of expanding urbanization, greater demand for livestock products, and a narrower supply response window. The aim of this research was to assess the dairy farm management practice and milk quality measurements using multi-source monitoring of the dairy farms. A pre-tested semi-structured questionnaire was used to collect primary data on dairy farm management practices by using simple cluster sampling techniques. Milk samples were acquired from bulk and individual cows at the peak, mid, and late stages of lactation. Feeds were collected in three phases and if there is no difference in feeds, the feed sample becomes blended into one pooled composite sample and taken into the laboratory for quality estimation. The research result revealed that the number of dairy cows varies substantially within and between dairy farm groups, ranging from 5-50, 3-42, and 5-45 dairy cows reported in Bahir Dar, D/tabor and Gondar cities, respectively, with an average number of 15.46±2.47, 13±1.33 and 12.83±1.72 dairy cows reported in the same order. According to a descriptive examination, the lactoscan laboratory result of the bulk tank milk (BTM), (2.82±0.32 and 2.81±0.38 %) had the highest mean values of fat and protein contents in Bahir Dar, D/tabor and Gondar cities respectively. In the individual cow milk (ICM) analysis, Gondar had the highest mean fat value (5.04±0.9%), while Bahir Dar had the highest mean value was protein (3.99±.59). The common feed identified in the entire area of the current study was TMR and NSC, and the CP contents in the feed sample analysis revealed a variation in TMR and NSC of (14.94 and 37.92%), (16.56 and 33.67%), and (20.38 and 35.24%) found in Gondar, D/tabor, and Bahir Dar cities respectively. In contrast, the fat-to-protein ratio was BTM 1.06±.085, 0.99±.061, and 1.055±.89%, respectively. Hence, the standard fat to protein ratio becomes 1-1.5, while, Debre tabor (DT) failed to achieve the fat to protein ratio (FPR) required standards as a whole. Since the fat and protein content were below the standards (3.5 to 4 and 3 to 3.5% respectively), farmers must re-evaluate feed quality, and the FPR of DT is below the requirement, which affects the energy balance of the cow, which needs the feeding practice should be adjusted to meet the required standards.